Seborrheic Keratosis: Report of a Rare Presentation and Reminder of the Current Knowledge of the Problem - Bahaeddine Lahbacha; Salwa Nechi; Abir Chaabane; Amina Bani; Majdi Kchaou; Fadhel Chtourou; Mohamed Karim Mfarrej; Amel Douggaz; Emna Chelbi (SAGE Publishing, 2024)
A 75-year-old man presented with an abdominal enlarging painless tumor of the skin evolving over the last 30 years. His past medical history was unremarkable. Physical examination revealed a brownish pedunculated cutaneous mass which had an irregular keratotic warty surface with no discharge or ulceration. The mass was clinically presumed to be a melanocytic tumor, or a verrucous carcinoma. A monoblock excision of the mass was performed with a good outcome. The specimen was then sent to our pathology department to rule out malignancy. Macroscopic examination revealed a brownish tumor of 7.5 × 7 × 1.5 cm which had fissures and cauliflower-like appearance. Final histological report concluded to a giant seborrheic keratosis.